PERSEPSI LINGKUNGAN KERJA DAN STRESS KERJA KARYAWAN DI PABRIK GULA JEMBER - Wahyuni (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2022)
This study involved 140 respondents. The results of the study show the coefficient value (r) of F = 9,654, with P = 0.000 (p < 0.01). This means that the hypothesis proposed by the researcher is accepted. Perceptions of the conditions of the work environment in this study are classified as positive, this was indicated by the empirical mean of 128.00 which was in the positive category, while the level of work stress in this study was relatively low, this was indicated by the results of the Z test of 75.8 which was located in the low category. The effective contribution of perceptions of the conditions of the work environment is 42.1% to the level of work stress in employees, which is indicated by an r2 of 0.421. This means that there are still 57.9% of other factors that affect the level of work stress of employees in the production division outside the variable perception of the conditions of the work environment. Keywords: work stress, perception, work environment